Dorsal Bed Nucleus of the Stria Terminalis-Subcortical Output Circuits Encode Positive Bias in Pavlovian Fear and Reward - Kaouane, Nadia; Ada, Sibel; Hausleitner, Marlene; Haubensak, Wulf (Frontiers in Neural Circuits, 2021)
Opposite emotions like fear and reward states often utilize the same brain regions. The bed nucleus of the stria terminalis (BNST) comprises one hub for processing fear and reward processes. However, it remains unknown how dorsal BNST (dBNST) circuits process these antagonistic behaviors. Here, we exploited a combined Pavlovian fear and reward conditioning task that exposed mice to conditioned tone stimuli (CS)s, either paired with sucrose delivery or footshock unconditioned stimuli (US). Pharmacological inactivation identified the dorsal BNST as crucial element for both fear and reward behavior. Deep brain calcium imaging revealed opposite roles of two distinct dBNST neuronal output pathways to the periaqueductal gray (PAG) or paraventricular hypothalamus (PVH). dBNST neural activity profiles differentially process valence and Pavlovian behavior components: dBNST-PAG neurons encode fear CS, whereas dBNST-PVH neurons encode reward responding. Optogenetic activation of BNST-PVH neurons increased reward-seeking, whereas dBNST-PAG neurons attenuated freezing. Thus, dBNST-PVH or dBNST-PAG circuitry encodes oppositely valenced fear and reward states, while simultaneously triggering an overall positive affective response bias (increased reward-seeking while reducing fear-responses). We speculate that this mechanism amplifies reward-responding and suppresses fear-responses linked to BNST dysfunction in stress and addictive behaviors.